Producing high quality examination paper with R-value using Rasch model / Mohd Nor Mamat … [et al.] - Mamat, Mohd Nor; Mahamood, Siti Fatahiyah; Mokhtar, Fattawi; Maidin, Pisol (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Measurement of student's performance must be assessed for right and desired learning outcomes, using right and reliable instrument, scientifically tested and reliably validated. In term of producing examination question set, our current practice is very much dependent on experts or vetters to identify the best set of questions to be distributed. Dislike of that, this simple procedure uses Rasch model and Winsteps software to evaluate the reliability of question set and difficulty ranks of the question item, to be fixed or preset the weightage. This proposes a very simplified procedure which is easily applied by all teachers or lecturers, and it offers reliable solution in producing high quality exam paper, with scientific r value for each and overall question construct.